The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00223-017-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Mineral Density, Bone Turnover Markers, and Vertebral Fractures with All-Cause Mortality in Type 2 Diabetes Mellitus

Abstract: Patients with type 2 diabetes mellitus (T2DM) have an increased risk of fragility fracture. However, the association between diabetes-related osteoporosis and mortality in T2DM remains unknown. This historical cohort study assessed the endpoint of all-cause mortality in patients with T2DM. According to our hospital record, bone parameters were examined in 797 patients from 1997 to 2009. We excluded 78 because of diseases affecting bone metabolism and could not follow-up 308 patients. Finally, in 411 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…With the increasing prevalence of T2DM and osteoporosis, the relationship between T2DM and bone metabolism has increasingly become the focus of research. 2,4 Metabolic disorders induced by T2DM tend to affect bone metabolism in different ways. 4,26 However, there is no consensus about the changes in BMD in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing prevalence of T2DM and osteoporosis, the relationship between T2DM and bone metabolism has increasingly become the focus of research. 2,4 Metabolic disorders induced by T2DM tend to affect bone metabolism in different ways. 4,26 However, there is no consensus about the changes in BMD in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) tends to be associated with higher bone mineral density (BMD) and, illogically, with an increase in bone fragility. [1][2][3] It is increasingly recognized that postmenopausal women with T2DM have a high fracture risk that is associated with osteoporosis 1,4 and that previously established methods for predicting fracture events can be very variable in patients with T2DM because a higher BMD is associated with increased fracture events in these patients. 5 Conceptually, osteoporosis is defined as a systemic skeletal disease that is characterized by bone mass impairment and micro-architectural deterioration of bone tissue with a consequent decrease in bone strength and susceptibility to fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the risk of fracture in T2D patients has attracted increasing attention . For T2D patients, severe vertebral fractures may even be related to all‐cause mortality . Bone mineral densities (BMDs) measured with dual‐energy X‐ray absorptiometry (DXA) indicate the risk of fractures for non‐diabetic patients, but may underestimate fracture risk in T2D patients because T2D patients may experience fractures at relative elevated BMDs compared with non‐diabetics .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For T2D patients, severe vertebral fractures may even be related to all-cause mortality. 6 Bone mineral densities (BMDs) measured with dualenergy X-ray absorptiometry (DXA) indicate the risk of fractures for non-diabetic patients, but may underestimate fracture risk in T2D patients because T2D patients may experience fractures at relative elevated BMDs compared with non-diabetics. 7 Moreover, various diabetes therapies may affect bone metabolism, 8 which poses a huge challenge to the clinical management of fracture risk in T2D patients.…”
Section: Introductionmentioning
confidence: 99%
“…Many confounding factors are present, including those relating to the measurement of areal BMD (aBMD), and the complex interactions that exist between bone, body weight, and metabolism in T2D. A cohort study including 222 men and 189 women with T2D reported an inverse association between lumbar spine and femoral neck aBMD measured by Dual X-ray Absorptiometry (DXA) and all-cause mortality, and a positive association of severe vertebral fractures and mortality [6]. These observations require confirmation in larger cohorts and using more specific measures including volumetric BMD (vBMD) measured with Quantitative Computed Tomography (QCT).…”
Section: Introductionmentioning
confidence: 99%